(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
In Mongolia, approximately 6,250 tons or 1.6 million lead-acid batteries are discarded annually. Of these, only 19% are recycled under poor conditions and exported, while the remaining 80% are improperly disposed into the environment, contributing significantly to soil, air, and water pollution. This study was conducted to determine the levels, vertical distribution, and chemical fractions of heavy metals in soils around a battery recycling plant in Nalaikh District, Ulaanbaatar, and to assess their environmental risks. A total of 78 soil samples were collected and analyzed for eight heavy metals (Cr, Cu, Pb, Ni, Zn, Co, As, Cd) using standard methods. The mobility of metals was assessed using sequential extraction. The results revealed that, except for Pb and As, most metals were within the permissible limits of MNS 5850:2019, though slightly elevated compared to control samples. The Pb concentration in the surface soil (0–5 cm) exceeded the standard by 52.6 times and the hazardous level by 687 mg/kg. Furthermore, 79.7% of Pb was in a mobile form, indicating high potential for environmental contamination. The enrichment factor (EF) of Pb was 18.5, and the geoaccumulation index (Igeo) ranged between 0.77 and 3.45, indicating moderate to heavy pollution. These findings confirm that contamination originates mainly from human activities, particularly from poor battery recycling practices. This study provides a detailed assessment of total and mobile heavy metal fractions, highlighting the urgent need to implement appropriate remediation technologies and protective measures such as fume capture systems.